A Clinical Case of Thoracopagus Conjoined Twins - Nofiandi, Riki; Febriani, Febriani (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Conjoined twins result from the incomplete division of a single fertilized egg, with an incidence of approximately 1 in 200,000 live births. This rare congenital anomaly presents significant anatomical and physiological challenges, necessitating a multidisciplinary approach for diagnosis, management, and ethical considerations. Case Presentation: A pair of thoracopagus conjoined twins was delivered at Arifin Achmad General Hospital following preterm labor complicated by premature rupture of membranes (PROM). Prenatal ultrasound identified shared thoracic and abdominal structures, including cardiac and vascular abnormalities. The twins exhibited severe congenital anomalies, such as cardiomegaly and ventriculomegaly. Despite immediate resuscitation efforts, both infants succumbed due to extensive anatomical complications.Conclusion: The prognosis of thoracopagus twins remains poor, particularly in cases with extensive organ fusion. Advances in prenatal imaging and fetal surgery may improve outcomes in select cases; however, a multidisciplinaryand compassionate approach remains essential for optimal perinatal care. Keywords: Conjoined twins, Thoracopagus, Prenatal diagnosis, Ethical challenges, Perinatal managementKasus Klinis Bayi Kembar Siam Tipe ThoracopagusAbstrakPendahuluan: Kembar siam terjadi akibat pembelahan zigot yang tidak sempurna, dengan insiden 1 dari 200.000 kelahiran hidup. Anomali kongenital langka ini menimbulkan tantangan kompleks dalam aspek anatomi, fisiologi,serta etika sehingga memerlukan pendekatan multidisiplin dalam diagnosis dan penatalaksanaan. Laporan Kasus: Sepasang kembar siam thoracopagus lahir prematur di RSUD Arifin Achmad akibat persalinan preterm yang disertai ketuban pecah dini (KPD). Pemeriksaan ultrasonografi prenatal mendeteksi fusi struktur torako-abdominal, termasuk keterlibatan organ jantung dan pembuluh darah utama. Bayi mengalami kelainan kongenital berat kardiomegali dan ventrikulomegali. Meskipun dilakukan resusitasi segera, keduanya tidak bertahan hidup akibat komplikasi anatomi yang luas. Kesimpulan: Prognosis kembar siam thoracopagus tetap buruk, terutama pada kasus dengan keterlibatan organ yang luas. Kemajuan dalam pencitraan prenatal dan pembedahan janin dapat meningkatkan harapan hidup dalam kondisi tertentu; namun, pendekatan multidisiplin yang komprehensif dan penuh empati tetap menjadi kuncidalam perawatan perinatal.